Assessment of tumor morphology on diffusion‐weighted (DWI) breast MRI: Diagnostic value of reduced field of view DWI. Issue 6 (24th April 2015) - Barentsz, Maarten W.; Taviani, Valentina; Chang, Jung M.; Ikeda, Debra M.; Miyake, Kanae K.; Banerjee, Suchandrima; van den Bosch, Maurice A.A.J; Hargreaves, Brian A.; Daniel, Bruce L.
Abstract : Purpose: To compare the diagnostic value of conventional, bilateral diffusion‐weighted imaging (DWI) and high‐resolution targeted DWI of known breast lesions. Materials and Methods: Twenty‐one consecutive patients with known breast cancer or suspicious breast lesions were scanned with the conventional bilateral DWI technique, a high‐resolution, reduced field of view (rFOV) DWI technique, and dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) (3.0 T). We compared bilateral DWI and rFOV DWI quantitatively by measuring the lesions' apparent diffusion coefficient (ADC) values. For qualitative comparison, three dedicated breast radiologists scored image quality and performed lesion interpretation. Results: In a phantom, ADC values were in good agreement with the reference values. Twenty‐one patients (30 lesions: 14 invasive carcinomas, 10 benign lesions [of which 5 cysts], 3 high‐risk, and 3 in situ carcinomas) were included. Cysts and high‐risk lesions were excluded from the quantitative analysis. Quantitatively, both bilateral and rFOV DWI measured lower ADC values in invasive tumors than other lesions. In vivo, rFOV DWI gave lower ADC values than bilateral DWI (1.11 × 10 ‐3 mm 2 /s vs. 1.24 × 10 ‐3 mm 2 /s, P = 0.002). Regions of interest (ROIs) were comparable in size between the two techniques (2.90 vs. 2.13 cm 2, P = 0.721). Qualitatively, all three radiologists scored sharpness of rFOV DWI images as significantly higher than bilateral DWI ( P ≤ 0.002). Receiver operating characteristic (ROC) curve analysis showed a higher area under the curve (AUC) in BI‐RADS classification for rFOV DWI compared to bilateral DWI (0.71 to 0.93 vs. 0.61 to 0.76, respectively). Conclusion: Tumor morphology can be assessed in more detail with high‐resolution DWI (rFOV) than with standard bilateral DWI by providing significantly sharper images. J. MAGN. RESON. IMAGING 2015. J. MAGN. RESON. IMAGING 2015;42:1656–1665.